Composite glass fiber material comprising thermosetting polymer
By using N-vinyloxazolidinone as a reactive diluent and combining with ethylenically unsaturated resin, the disadvantages of the reactive diluent in the prior art are solved, and a composite glass fiber material with high polarity and high impact strength is achieved.
Patent Information
- Application Number
- CN202380064308.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-18
AI Technical Summary
Existing reactive diluents have problems such as residual monomers, hydrolysis ease, low reactivity and viscosity when producing composite glass fiber materials, and styrene is questioned for odor and toxicity issues.
A curable resin composition containing N-vinyloxazolidinone as a reactive diluent is used to form a composite material with high polarity and high compatibility by combining it with an ethylenically unsaturated resin.
The good solubility of highly polar ethylenically unsaturated resin is achieved, reducing the toxicity and odor problems of the material, and improving the impact strength of the composite glass fiber material.
Smart Images

Figure CN119855861A_ABST
Abstract
Description
[0001] The present invention relates to a composite glass fiber material comprising a thermosetting polymer, a method for producing a composite glass fiber material, the use of N-vinyl oxazolidone in the method for obtaining a composite glass fiber material, and a curable resin composition.
[0002] Composite fiber materials comprise a fiber-reinforced polymer matrix and are used, for example, as molded parts in a wide variety of applications, including automotive construction and engineering. The polymer of the composite fiber material is typically a thermosetting polymer, such as an epoxy, vinyl ester or polyester thermosetting polymer.
[0003] EP 3 626 759 A1 describes high-temperature unsaturated polyester (UP) resins based on cyclic and acyclic raw materials and describes in detail the use of such resins in various fields.
[0004] The production of composite fiber materials containing thermosetting polymers involves the curing of prepolymer resins. The prepolymer resin is suitably ductile or liquid before curing. In order to optimize the rheology and thereby improve the processability of the resin, at least one reactive diluent (viscosity reducer) is usually added to the resin. During the curing of the resin, the reactive diluent copolymerizes with the resin.
[0005] Reactive diluents are typically low viscosity, monofunctional, difunctional or polyfunctional monomers or oligomers. Examples of frequently used reactive diluents include styrene and styrene derivatives, vinyl ethers, acrylates and methacrylates, especially styrene.
[0006] However, the use of common reactive diluents has several disadvantages. For example, styrene derivatives may produce a large amount of residual monomers, vinyl ethers are easily hydrolyzed, methacrylates exhibit relatively low reactivity, and acrylates may cause stickiness in the obtained polymer. In addition, the use of styrene, in particular, is considered problematic due to odor problems and concerns about its toxicity.
[0007] There is a need for additional composite fiber materials obtained from reactive diluents that address at least some of the above-mentioned disadvantages.
[0008] The present invention provides a composite glass fiber material comprising a thermosetting polymer, wherein the thermosetting polymer is obtained from a curable resin composition comprising:
[0009] (i) ethylenically unsaturated resins; and
[0010] (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I)
[0011]
[0012] Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms;
[0013] Wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-%, relative to the total amount of reactive diluent (ii) and the further reactive diluent.
[0014] It has been found that the composite glass fiber material comprising a thermosetting polymer can be advantageously obtained by a curable resin composition comprising a reactive diluent (ii). A special advantage is that the N-vinyl oxazolidinone with formula (I) dissolves the ability of an unsaturated resin with relatively high polarity. Without wishing to be bound by theory, it is assumed that the high polarity of the N-vinyl oxazolidinone with formula (I) makes these compounds highly compatible with the unsaturated resin of relative polarity. In addition, and unlike, for example, styrene, the N-vinyl oxazolidinone with formula (I) generally exhibits low toxicity and is almost tasteless, particularly 5-methyl-3-vinyl-oxazolidinone-2-one.
[0015] In the N-vinyl oxazolidinone of formula (I), part R 1 , R 2 , R 3 and R 4 Independently of one another, selected from a hydrogen atom and an organic moiety comprising 1 to 10 carbon atoms. The organic moiety preferably comprises 1 to 8 carbon atoms, more preferably 1 to 6 carbon atoms, most preferably 1 to 4 carbon atoms, such as 1 to 3 carbon atoms. The organic moiety may contain heteroatoms, such as oxygen, nitrogen and / or sulfur, in particular oxygen and / or nitrogen.
[0016] The organic part is preferably selected from C1-C 10 Alkyl and C1-C 10 Alkoxy, more preferably selected from C1-C4 alkyl and C1-C4 alkoxy, most preferably C1-C4 alkyl. Preferably, the organic part is selected from methyl, ethyl and propyl, more preferably selected from methyl and ethyl, most preferably methyl.
[0017] In a preferred embodiment, the N-vinyl oxazolidinone having formula (I) is characterized in that
[0018] -R 1 , R 2 , R 3 and R 4 At least two of them are hydrogen atoms, such as R 1 , R 2 , R 3 and R 4each of is a hydrogen atom; or
[0019] -R 1 is C1-C4 alkyl, preferably methyl, and R 2 , R 3 and R 4 is a hydrogen atom; or
[0020] -R 4 is C1-C4 alkyl, preferably methyl, and R 1 , R 2 and R 3 is a hydrogen atom; or
[0021] -R 1 and R 2 is a hydrogen atom, and R 3 and R 4 is C1-C4 alkyl, preferably methyl.
[0022] The synthesis of N-vinyl oxazolidinone compounds with formula (I) is well known in the art. For example, N-vinyl oxazolidinone compounds can be produced by pyrolysis of N-(1-hydroxyalkyl)-2-oxazolidinone according to US 4,831,153. In particular, N-vinyl oxazolidinone compounds can be synthesized by reaction of acetylene with oxazolidinone compounds (so-called "Reppe chemistry").
[0023] Preferred N-vinyloxazolidinones of formula (I) include 3-vinyloxazolidin-2-one (NVO) and vinylmethyloxazolidinones, such as 4-methyl-3-vinyl-oxazolidin-2-one (4-NVMO) and 5-methyl-3-vinyl-oxazolidin-2-one (5-NVMO), especially 5-methyl-3-vinyl-oxazolidin-2-one.
[0024] Vinylmethyloxazolidinone is commercially available. For example, from BASF SE Mainly comprises 5-methyl-3-vinyl-oxazolidin-2-one, and additionally comprises 4-methyl-3-vinyl-oxazolidin-2-one. In one embodiment, vinylmethyloxazolidinone comprises 5-methyl-3-vinyl-oxazolidin-2-one and up to 20 wt.-%, preferably up to 10 wt.-%, more preferably up to 5 wt.-% of 4-methyl-3-vinyl-oxazolidin-2-one, such as up to 1 wt.-%, or up to 0.05 wt.-% of 4-methyl-3-vinyl-oxazolidin-2-one based on the total amount of vinylmethyloxazolidinone.
[0025] Preferably, the reactive diluent (ii) comprises a total amount of 3-vinyloxazolidin-2-one, 5-methyl-3-vinyl-oxazolidin-2-one and 4-methyl-3-vinyl-oxazolidin-2-one in an amount of at least 90 mol-%, more preferably at least 95 mol-%, most preferably at least 98 mol-%, relative to the total amount of reactive diluent (ii). In a particularly preferred embodiment, the reactive diluent (ii) comprises 5-methyl-3-vinyl-oxazolidin-2-one and 4-methyl-3-vinyl-oxazolidin-2-one in an amount of at least 90 mol-%, more preferably at least 95 mol-%, most preferably at least 98 mol-%, relative to the total amount of reactive diluent (ii).
[0026] The curable resin composition comprises an ethylenically unsaturated resin. An ethylenically unsaturated resin carries an ethylenically unsaturated double bond in its backbone. In this context, the term "ethylenically unsaturated" refers to a moiety carrying an olefin C-C=C- double bond that is not part of an aromatic ring and is therefore susceptible to free radical polymerization. Typically, the ethylenically unsaturated double bond is present as a vinyl (-CH=CH-) double bond or a vinylidene (>C=CH2) double bond.
[0027] The ethylenically unsaturated resin (i) is preferably selected from the group consisting of ethylenically unsaturated polyester resins, vinyl ester resins, and urethane (meth)acrylate resins. In particular, the ethylenically unsaturated resin (i) is an ethylenically unsaturated polyester resin.
[0028] The ethylenically unsaturated polyester resin can be obtained by reacting: (ia) at least one unsaturated dicarboxylic acid, or an ester or anhydride thereof, wherein the unsaturated dicarboxylic acid comprises at least one ethylenically unsaturated dicarboxylic acid; and (ib) at least one polyol. Alternatively, the monomers used to form the ethylenically unsaturated polyester resin may comprise a saturated dicarboxylic acid or an ester thereof. The ethylenically unsaturated polyester resin carries ethylenically unsaturated double bonds in its backbone, which double bonds are derived from the polymerized ethylenically unsaturated dicarboxylic acid of component (ia).
[0029] In the context of unsaturated dicarboxylic acids and saturated dicarboxylic acids, the term "ester" may be any ester suitable for a polyester forming reaction. Typically, the term "ester" means an alkyl ester, in particular a C1-C4-alkyl ester and especially a methyl or ethyl ester.
[0030] The unsaturated dicarboxylic acid may be at least one ethylenically unsaturated dicarboxylic acid, which means that it has at least one ethylenically unsaturated double bond as described herein. The unsaturated dicarboxylic acid may also be a combination of at least one ethylenically unsaturated dicarboxylic acid and one or more aromatic dicarboxylic acids. The unsaturated dicarboxylic acid preferably comprises at least 50 mol-%, in particular at least 80 mol-%, of at least one ethylenically unsaturated dicarboxylic acid, based on the total amount of the unsaturated dicarboxylic acids.
[0031] Those skilled in the art will readily appreciate that in the formation of ethylenically unsaturated polyesters, any dicarboxylic acid may also be used in the form of its ester or its anhydride.
[0032] The olefinically unsaturated dicarboxylic acid comprises two carboxyl groups and at least one olefinically unsaturated moiety, i.e. a moiety with an olefinic double bond which is not part of an aromatic ring and which is therefore susceptible to free radical polymerization. Typically, the olefinically unsaturated double bonds of the olefinically unsaturated dicarboxylic acid are present as vinyl (-CH=CH-) double bonds or vinylidene (>C=CH2) double bonds. The olefinically unsaturated dicarboxylic acid may be linear or branched. The olefinically unsaturated dicarboxylic acid preferably comprises 4 to 8 carbon atoms, more preferably 4 to 7 carbon atoms, most preferably 4 or 5 carbon atoms.
[0033] Aromatic dicarboxylic acids suitable for combination with at least one ethylenically unsaturated dicarboxylic acid preferably contain 6 to 9 carbon atoms, more preferably 6 to 8, most preferably 8. Suitable aromatic dicarboxylic acids include phthalic acid, isophthalic acid and terephthalic acid.
[0034] Compound (ia) is preferably selected from maleic acid, maleic anhydride, fumaric acid, dimethyl fumarate, itaconic acid, dimethyl itaconate, mesaconic acid, citraconic acid, and tetrahydrophthalic anhydride, or a combination of at least one of the compounds and at least one compound selected from the following: phthalic acid, phthalic anhydride, isophthalic acid, terephthalic acid, dimethyl terephthalate, 2,5-furandicarboxylic acid and dimethyl 2,5-furandicarboxylate. Compound (ia) is more preferably selected from maleic acid, maleic anhydride, fumaric acid, itaconic acid and tetrahydrophthalic anhydride, and most preferably selected from fumaric acid and maleic anhydride.
[0035] In one embodiment, the ethylenically unsaturated polyester resin can be obtained in the presence of a saturated aliphatic dicarboxylic acid. Suitable saturated dicarboxylic acids are particularly aliphatic dicarboxylic acids typically having 4 to 14 carbon atoms, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid and tridecanedioic acid. Suitable saturated dicarboxylic acids also include alicyclic dicarboxylic acids typically having 6 to 14 carbon atoms, such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid or 1,4-cyclohexanedicarboxylic acid. Typically, the amount of saturated dicarboxylic acids will not exceed 50 mol-%, and preferably will not exceed 20 mol-%, of the total amount of dicarboxylic acids used in the reaction to form the ethylenically unsaturated polyester.
[0036] The at least one polyol (ib) is an organic compound comprising a plurality of hydroxyls. Preferably, the polyol (ib) comprises 2 to 5 hydroxyls, more preferably 2 or 3 hydroxyls, most preferably 2 hydroxyls. The polyol (ib) can be straight or branched, preferably straight. The polyol (ib) can be saturated or unsaturated.
[0037] Suitable polyols include aliphatic polyols, such as glycols, i.e. aliphatic diols, like ethylene glycol, propylene glycol, diethylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,3-propylene glycol, dipropylene glycol and neopentyl glycol; triols, such as glycerol; and aliphatic sugar alcohols, such as sorbitol, xylitol and erythritol; and heterocyclic polyols, in particular heterocyclic polyols containing at least one ring oxygen atom, such as maltitol or isosorbide. Diols and heterocyclic polyols are particularly preferred.
[0038] A particularly preferred polyol is isosorbide. Preferably, polyol (ib) comprises isosorbide in a total amount of at least 30 mol-%, more preferably at least 40 mol-%, most preferably at least 70 mol-%, such as at least 90 mol-% or at least 99 mol-%, relative to the total amount of polyol (ib).
[0039] The ethylenically unsaturated polyester resin (i) is preferably obtainable by reacting compounds (ia) and (ib) in a molar ratio ranging from 1.2:1 to 1:1.2, more preferably 1.1:1 to 1:1.1, most preferably 1.05:1 to 1:1.05.
[0040] Alternatively, the ethylenically unsaturated resin (i) is a vinyl ester resin. Vinyl ester resins are obtainable by esterification of epoxy resins with (meth)acrylic acid. The term (meth)acrylic acid is understood herein to mean both acrylic acid and methacrylic acid.
[0041] The epoxy resin used to prepare the vinyl ester resin is preferably a polyglycidyl ether, which typically has an average of 2 to 4 glycidyl groups per molecule and may also have 1 to 4 esterifiable hydroxyl groups. Preferred vinyl ester resins are aromatic vinyl ester resins. Of these, preferred are the reaction products of aromatic polyglycidyl ethers, especially those based on novolac epoxy resins (such as epoxyphenol novolac (EPN) or epoxycresol novolac (ECN)) or based on bisphenols (such as bisphenol A or bisphenol F) with acrylic acid. In a typical embodiment, bisphenol A is reacted with epichlorohydrin to form an epoxide and then esterified with acrylic acid.
[0042] Particularly preferred is the number average molecular weight M n Vinyl ester resins in the range from 500 to 4000 g / mol. Particularly preferred are aromatic vinyl ester resins having on average 1.9 to 5, in particular 2 to 4, acrylate groups.
[0043] Unlike ethylenically unsaturated polyester resins, vinyl ester resins contain only terminal double bonds. The low number of double bonds allows thermosetting polymers to be obtained from vinyl ester resins, which exhibit a relatively low crosslinking density and therefore high impact strength, elongation at break and tensile strength. In addition, compared to polymers obtained from ethylenically unsaturated polyester resins, thermosetting polymers obtained from vinyl ester resins exhibit fewer free chain ends and are therefore less susceptible to hydrolysis and more corrosion resistant. In addition, the glass transition of thermosetting polymers obtained from vinyl ester resins is more concentrated than the glass transition of thermosetting polymers obtained from ethylenically unsaturated polyester resins.
[0044] Suitable commercially available vinyl ester resins include in particular the vinyl ester resins from BASF AG. Products LR8765 (aliphatic), LR8986, LR9019, LR9023, EA9081, EA9082, EA9097, EP9124, EA9138, EA9143 and EA9145, EA9148; from DSM Coating Resins BV Products 1010, 1030, 2020, 3010, 3020, 3051, 9720, 9721, 9750, 9760, 9771, 9790, and 9792; from Allnex Sarl Products 113, 600, 604, 605, 608, 609, 640, 641, 648, 860, 1606, 1608, 3105, 3203, 3300, 3416, 3420, 3608, 3639, 3700, 3700, 3701, 3702, 3703, 3708, 3730, 3740, 5848, and 6040; from Eternal Chemical Co. Ltd. Products 621, 621, 622, 622, 623, 623, 624, 624, 625, 923, 6209, 6210, 6211, 6213, 6215, 6219, 6231, 6233, 6233, 6234, 6235, 6241, 6261, and 620; from IGM Products 3005, 3015, 3016, 3072, 3316, 3317, 3620, and 3660; from Miwon Specialty Chemical Co., Ltd. and Products Miramer PE 110H, Photocryl E 202, Photocryl E 203 / 30PE, Photocryl E 207 / 25TP, Photocryl E 207 / 30PE, Photocryl E 07 / 25HD, Miramer PE 210, Miramer PE 210HA, Miramer PE 230, Miramer PE 250, Miramer PE 250LS, Photocryl DP 296, Miramer PE 310, Photocryl DP460, Miramer PE 2100, Miramer PE 2120A, Miramer PE 2120 C, Miramer PE 2120B, Miramer PE 130, Miramer ME 2500, Miramer SC 6345, and Miramer SC 6400; from Rahn AG Products 2235, 2253, 2255, 2259, 2263, and 2280; from Sartomer CN and Products Sartomer CN 104Y50, Sartomer CN 108, Sartomer CN 109, Sartomer CNUVE 110 / 95, Sartomer CN 111, Sartomer CN 112B70, Sartomer CN12C60, Sartomer CN 113D70, Sartomer CNUVE 114 / 95, Sartomer CN 115, Sartomer CN116, Sartomer CN 116D50, Sartomer CN 117, Sartomer CN 118, Sartomer CN 119, Sartomer CN 120, Sartomer CN 120A75, Sartomer CN 120A80, Sartomer CN 120B60, Sartomer CN 120B80, Sartomer CN 120 C60, Sartomer CN 120 C80, Sartomer CN120D80, Sartomer CN 120E50, Sartomer CN 120J90, Sartomer CN 120M50, Sartomer CN120S80, Sartomer CN 121, Sartomer CN 122A80, Sartomer CN 124, Sartomer CN 129, Sartomer CNUVE 130, Sartomer CN 131B, Sartomer CN 132, Sartomer CN 133, SartomerCN 136, Sartomer CN 148, Sartomer CNUVE 150 / 80, Sartomer CN 151, Sartomer CNUVE151, Sartomer CN 152, Sartomer CN 56, Sartomer CN 159, Sartomer CN 173, SartomerCN 186, Kayarad R 190, Kayarad R 205, Kayarad TCR 1094, Kayarad TCR 1096, SartomerCN 1300, Sartomer CN 2003EU, Kayarad EAM 2160, and Kayarad EAM 2300, and those from Qualipoly Chemical Corporation GU products GU1160C, GU1200W, GU1280A, GU1380A, GU1400Z, GU1475A, GU1480A, GU1600Y, GU1650X, GU1700W, GU1700P, GU1700T, GU1700Y, GU1700Z, GU1800W, GU1900W, and GU1900Z, which in some cases are blends with monomers.
[0045] Alternatively, the ethylenically unsaturated resin (i) is a urethane (meth) acrylate resin. Urethane (meth) acrylates can be obtained by reacting an aromatic or aliphatic diisocyanate or oligomeric isocyanate with a hydroxyalkyl (meth) acrylate (such as hydroxyethyl (meth) acrylate or hydroxypropyl (meth) acrylate), and optionally a saturated polyol selected from aliphatic polyols, alicyclic polyols, polyether alcohols, polyester alcohols, polyetherester alcohols and polycarbonate diols.
[0046] Suitable commercially available urethane (meth)acrylate resins include urethane (meth)acrylates, more particularly oligomers and polymers, which contain urethane groups, have an average of 1.8 to 10, more particularly 1.9 to 8.5 (meth)acrylate groups, and are preferably obtainable by reaction of aromatic or aliphatic diisocyanates or oligomeric isocyanates with hydroxyalkyl (meth)acrylates. Examples thereof are BASF AG's Products UA19T, UA9028, UA9030, UA8987, UA9029, UA9033, UA9047, UA9048, UA9050, UA9072, UA9065, UA9089, UA9073, and UA9136; from DSM Coating Resins U products 10, 20, 25, 42, 60, 61, 6282, and 6288; from DSM Coating Resins Products 230, 236, 250, and 670; from Allnex LLC Products 204, 205, 206, 210, 214, 215, 220, 221, 230, 244, 245, 246, 264, 265, 267, 270, 271, 280, 284, 285, 286, 294, 1258, 1290, 1290, 1291, 2002, 2003, 2221, 4101, 4150, 4201, 4220, 4250, 4265, 4396, 4491, 4501, 4510 , 4513, 4587, 4654, 4666, 4680, 4683, 4740, 4765, 4820, 4858, 4859, 5021, 5129, 6202, 8100, 8110, 8210, 8213, 8215, 8232, 8254, 8296, 8301, 8307, 8310, 8311, 8402, 8405, 8413, 8415, 8465, and 8602; from Changxing Chemical Co., Ltd. Products 611, 615, 6072, 6081, 6101, 6112, 6113, 6114, 6115, 6120, 6121, 6122, 6123, 6127, 6130, 6131, 6134, 6141, 6142, 6143, 6144, 6145, 6145, 6146, 6147, 6148, 6148, 6149 ,6150,6151,6152,6153,6153,6154,6154,6157,6158,6160,6161,6164,6165,617 0, 6171, 6172, 6175, 6175, 6175, 6176, 6181, 6195, 6196, 6197, 6198, 8000, Etercure DR-U 6-1, Etercure DR-U 10, Etercure DR-U 11, Etercure DR-U20, Etercure DR-U 21, EtercureDR-U 22, Etercure DR-U 24, Etercure DR-U 25, Etercure DR-U 26, Etercure DR-U 57. Etercure DR-U 91, Etercure DR-U 92, Etercure DR-U 95, Etercure DR-U 106, EtercureDR-U 116, Etercure DR-U 300, Etercure DR-U 301; from IGM Resins BV Products 6008, 6009, 6010, 6019, 6184, 6210, 6230, 6625, 6628, 6690, 6720, 6891, 6892, and 6893; from Meiyuan Specialty Chemicals Co., Ltd. Products 256, 307, 320, 340, 360, 375, 610, 620, 622, 662, 664, 2012, 2030, 2100, 2152, 2200, 2404, 2410, 2421, 2510, 2560, 2564, 2565, 2900, 3100, 3195, 3201, 3280, 3304, 3400, 3420, 3440, 3450, 3600, 3603, 3701, 3710, 3722, 4100, 4150, 5000, 5216, 6140, and 9800; from Ruion Products 1122, 4188, 4205, 4215, 4217, 4256, 4267, 4269, 4297, 4302, 4312, 4316, 4425, 4590, and 4622; from Sartomer CN products 902, 910, 914, 916, 922, 925, 929, 936, 944, 945, 945, 945, 956, 959, 961, 961, 962, 963, 963, 963, 963, 964, 965, 966, 967, 968, 970, 971, 972, 973, 975, 976, 977, 978, 980, 981, 982, 983, 984, 985, 989, 990, 991, 992, 994, 996, 997, 998, 999 99, 1963, 3000, 3001, 8000, 8001, 8002, 8003, 9001, 9002, 9004, 9007, 9010, 9014, 9026, 9101, 9102, 9130, 9143, 9165, 9167, 9170, 9196, 9200, 9245, 9245, 9250, 9251, 9260, 9276, 9278, 9293, 9761, 9782, 9783, 9788, 9800, and 9893 from Guojing Chemical Co., Ltd. GU products GU3001Z, GU3010Z, GU3030Z, GU3100W, GU3100Y, GU3100Z, GU3185A, GU3185B, GU3285A, GU3290M , GU3300W, GU3300Z, GU3370A, GU3400Y, GU3400Z, GU3501Q, GU4000Y, GU4075B, GU4100Y, GU4175X, GU4 200Z, GU4280B, GU4300Y, GU4500Y, GU6100L, GU6200Y, GU6200Z, GU6300Y, GU6370F, GU7200Z, GU7400Z, GU7500Z, GU3680A, GU3700Y, GU3701W, GU3775A, GU3980A, GU4660A, GU4900Y, GU6600Y, and GU7900Z, and GS products GS4920C and GS5120C, which are in some cases blends with monomers. Among these, preferred are aliphatic urethane acrylates. Particularly preferred are number average molecular weight M n Aliphatic urethane (meth)acrylates in the range of 500 to 4,000 g / mol.
[0047] Suitable aliphatic polyols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, 1,4-butanediol and polytetrahydrofuran.
[0048] Suitable polyesterols may be derived from adipic acid and a polyol selected from the group consisting of ethylene glycol, propylene glycol, 1,4-butanediol, 1,4-hexanediol, diethylene glycol, and dipropylene glycol.
[0049] Suitable polycarbonate diols include polycarbonates based on 1,5-pentanediol and 1,6-hexanediol.
[0050] In one embodiment, the ethylenically unsaturated resin (i) has at least one of the following characteristics:
[0051] - a number average molecular weight (M) in the range of 500 to 10,000 g / mol n ), as determined by gel permeation chromatography;
[0052] - an acid value in the range of 5 to 80 mg KOH / g; and
[0053] - Hydroxyl number in the range of 5 to 80 mg KOH / g.
[0054] Preferably, the ethylenically unsaturated resin (i) has at least one of the following characteristics:
[0055] - a number average molecular weight (M) in the range of 800 to 8,000 g / mol, preferably 1,000 to 5,000 g / mol n ), as determined by gel permeation chromatography;
[0056] - an acid value in the range of 10 to 65 mg KOH / g, preferably 15 to 55 mg KOH / g; and
[0057] - a hydroxyl number in the range of 10 to 65 mg KOH / g, preferably 15 to 55 mg KOH / g.
[0058] The acid number (neutralization number) is the amount of potassium hydroxide (KOH) in milligrams required to neutralize one gram of ethylenically unsaturated resin. The acid number indicates the number of carboxylic acid groups per gram of compound and can be determined by DIN EN ISO 2114. The acid number is particularly relevant for the characterization of ethylenically unsaturated polyester resins.
[0059] The hydroxyl number is the amount of potassium hydroxide (KOH) (in milligrams) required to neutralize the acetic acid absorbed when one gram of a chemical substance containing free hydroxyl groups is acetylated. The hydroxyl number indicates the number of free hydroxyl groups per gram of a compound and can be determined by DIN EN ISO 4692-2.
[0060] In other embodiments, the ethylenically unsaturated resin (i) has a vinyl density in the range of 0.5 to 10 mol / kg, in particular
[0061] - when the ethylenically unsaturated resin (i) is an ethylenically unsaturated polyester resin, in the range of 2.0 to 9.0 mol / kg, such as 4.0 to 7.5 mol / kg;
[0062] - when the ethylenically unsaturated resin (i) is a vinyl ester resin, in the range of 1.0 to 4.5 mol / kg, such as 2.5 to 4.5 mol / kg;
[0063] - When the ethylenically unsaturated resin (i) is a urethane (meth)acrylate resin, in the range of 1.0 to 5.0 mol / kg, such as 3.0 to 5.0 mol / kg.
[0064] The vinyl density indicates the molar proportion of vinyl groups per kg of resin. The vinyl density can be determined by nuclear magnetic resonance (NMR) spectroscopy.
[0065] It was found that N-vinyl oxazolidinones having the formula (I) are particularly suitable for solubilizing the Hansen solubility parameter δ p At least 5.5MPa 1 / 2The ethylenically unsaturated resin (i) is preferably an ethylenically unsaturated polyester resin. This applies in particular when the ethylenically unsaturated resin is an ethylenically unsaturated polyester resin. The Hansen solubility parameter δ p Indicates the energy from the intermolecular dipole intermolecular forces.
[0066] Without wishing to be bound by theory, it is hypothesized that the high polarity of N-vinyl oxazolidinones of formula (I) makes these compounds highly compatible with relatively polar unsaturated resins, as reflected in the relatively high Hansen solubility parameters δ of these unsaturated resins. p superior.
[0067] The definition and calculation of solubility parameters in three-dimensional Hansen solubility space are described in CM Hansen: “The Three Dimensional Solubility parameter and Solvent Diffusion Coefficient–Their Importance in Surface Coating Formulation”, Danish Technical Press, Copenhagen, 1967.
[0068] As mentioned above, δ p represents the energy from the intermolecular dipole intermolecular forces, while δ d represents the energy from the intermolecular dispersion force, and δ h It represents the energy from hydrogen bonds between molecules. The unit of the parameter Hansen solubility parameter is MPa 1 / 2 .
[0069] Hansen solubility parameters for many compounds are listed in standard works such as "Hansen Solubility Parameters: A User's Handbook", C.M. Hansen, 2007, 2nd edition, CRC Press. Hansen solubility parameters can also be calculated based on the chemical structure of the compound using well-known modeling software such as HSPIP 3.1.25 (3rd edition) or COSMOquick 2021 developed and distributed by C.M. Hansen. The Hansen solubility parameters are calculated assuming that the room temperature is approximately 25°C. In this article, the Hansen solubility parameters, particularly δ p It is calculated according to the method described in the following working examples.
[0070] If the Hansen solubility parameter δ pBelow the required value, the solubility of the ethylenically unsaturated resin (i) in the N-vinyl oxazolidinone of formula (I) may be insufficient and the advantageous properties of the reactive diluent (ii) are less pronounced. In addition, it was found that the known reactive viscosity reducer styrene could not be reliably expressed as the Hansen solubility parameter δ p At least 5.5MPa 1 / 2 The ethylenically unsaturated resin (i) provides sufficient solubility.
[0071] In one embodiment, the ethylenically unsaturated resin (i) is characterized by a Hansen solubility parameter δ p At least 5.7MPa 1 / 2 , such as at least 6.0MPa 1 / 2 , or at least 6.3MPa 1 / 2 , more preferably at least 6.5 MPa 1 / 2 , especially at least 7.0 MPa 1 / 2 , most preferably at least 8.0 MPa 1 / 2 . Hansen solubility parameter δ p Preferably at most 16 MPa 1 / 2 , more preferably at most 12 MPa 1 / 2 , most preferably at most 8.5MPa 1 / 2 .
[0072] In further embodiments, the ethylenically unsaturated resin (i) is characterized by a Hansen solubility parameter δ d At least 15.0MPa 1 / 2 , preferably at least 17.0 MPa 1 / 2 , more preferably at least 17.5 MPa 1 / 2 , most preferably at least 18.0 MPa 1 / 2 , such as at least 18.5MPa 1 / 2 . Hansen solubility parameter δ d Preferably at most 22.0 MPa 1 / 2 , more preferably at most 20.5 MPa 1 / 2 , most preferably at most 19.5 MPa 1 / 2 .
[0073] In further embodiments, the ethylenically unsaturated resin (i) is characterized by a Hansen solubility parameter δ h At least 15.0MPa 1 / 2 , preferably at least 15.5 MPa 1 / 2 , more preferably at least 16.0 MPa 1 / 2 , most preferably at least 17.0 MPa 1 / 2 . Hansen solubility parameter δ h Preferably at most 30.0 MPa 1 / 2 , more preferably at most 24.0 MPa1 / 2 , most preferably at most 18.0 MPa 1 / 2 .
[0074] In one embodiment, the ethylenically unsaturated resin (i) is characterized by
[0075] -Hansen solubility parameter δ p At least 5.5MPa 1 / 2 , preferably at least 5.7 MPa 1 / 2 , such as at least 6.0MPa 1 / 2 , or at least 6.3MPa 1 / 2 , more preferably at least 6.5 MPa 1 / 2 , especially at least 7.0 MPa 1 / 2 , most preferably at least 8.0 MPa 1 / 2 ,as well as
[0076] -Hansen solubility parameter δ d At least 15.0MPa 1 / 2 , preferably at least 17.0 MPa 1 / 2 , more preferably at least 17.5 MPa 1 / 2 , most preferably at least 18.0 MPa 1 / 2 , such as at least 18.5MPa 1 / 2 .
[0077] The above upper limit is preferred.
[0078] In further embodiments, the ethylenically unsaturated resin (i) is characterized by
[0079] -Hansen solubility parameter δ p At least 5.5MPa 1 / 2 , preferably at least 5.7 MPa 1 / 2 , such as at least 6.0MPa 1 / 2 , or at least 6.3MPa 1 / 2 , more preferably at least 6.5 MPa 1 / 2 , especially at least 7.0 MPa 1 / 2 , most preferably at least 8.0 MPa 1 / 2 ;
[0080] -Hansen solubility parameter δ d At least 15.0MPa 1 / 2 , preferably at least 17.0 MPa 1 / 2 , more preferably at least 17.5 MPa 1 / 2 , most preferably at least 18.0 MPa 1 / 2 , such as at least 18.5MPa 1 / 2 ;as well as
[0081] -Hansen solubility parameter δ h At least 15.0MPa 1 / 2 , preferably at least 15.5 MPa 1 / 2 , more preferably at least 16.0 MPa 1 / 2 , most preferably at least 17.0 MPa 1 / 2 .
[0082] The above upper limit is preferred.
[0083] Parameter δ p , δ d and δ h Can be thought of as the coordinates of a point in three-dimensional space (also called Hansen space). The closer two molecules are in Hansen space, the more likely they are to dissolve each other. In order to determine if the parameters of two molecules (typically a solvent and a polymer) are within range, an interaction radius (or R0 value) is often attributed to the substances to be dissolved. The R0 value determines the radius of a sphere in Hansen space. All suitable solvents lie within the sphere, while unsuitable solvents lie outside the sphere.
[0084] The interaction radius R0 is the maximum distance R that a substance dissolves a The distance R a is calculated from the Hansen solubility parameters of the substance under consideration. Subsequently, experimental solubility tests were performed. The results are consistent with R a Theoretical calculation of the parameters is related. a The value of can be calculated by the following formula:
[0085]
[0086] How to determine R a A detailed discussion of R0 and R0 values can be found in "Hansen Solubility Parameters: A User's Handbook", CM Hansen, 2007, 2nd edition, CRC Press.
[0087] By R a and R0 value, according to RED=R a / R0 calculates the relative energy density (RED). If the RED value is less than 1, the substance will dissolve. If the RED value is 1, the substance will partially dissolve. If the RED value is greater than 1, the substance will not dissolve.
[0088] For example, the experimentally determined R0 value for styrene is 12.65. This means that if the R calculated from styrene and the Hansen parameters of a specific resin, for example a For values above 12.65, the RED value will be above 1 and the material will be insoluble in styrene.
[0089] In one embodiment, the ethylenically unsaturated resin (i) is characterized by R a The value is greater than 12.65, preferably greater than 12.70 or greater than 12.80.
[0090] If the Hansen Solubility Parameter values for the individual substances are known, the Hansen Solubility Parameter values for the mixture can be calculated. Each parameter is calculated individually by adding the parameters for the two substances according to the volume ratio:
[0091]
[0092] in is the volume fraction of substance 1, is the volume fraction of substance 2, and δ1 is the Hansen solubility parameter of substance 1 (δ d , δ p or δ h ) and δ2 is the Hansen solubility parameter of substance 2 (δ d , δ p or δ h For a given substance, there is an optimal solvent ratio (with the smallest distance R a ). Even two (or more) substances that are typically not suitable for dissolving a compound can become suitable solvents in certain proportions because the mixture can be located within the solubility sphere R0.
[0093] The curable resin composition preferably comprises the ethylenically unsaturated resin (i) in an amount of 15 to 85 wt.-%, more preferably 15 to 75 wt.-%, most preferably 20 to 60 wt.-%, based on the total weight of the curable resin composition.
[0094] The curable resin composition preferably comprises the reactive diluent (ii) in an amount of 0.5 wt.-% to 85 wt.-%, for example 3 wt.-% to 85 wt.-%, or 5 wt.-% to 85 wt.-%, preferably 10 wt.-% to 80 wt.-%, more preferably 15 wt.-% to 80 wt.-%, such as 20 wt.-% to 80 wt.-%, even more preferably 25 wt.-% to 80 wt.-%, most preferably 40 wt.-% to 80 wt.-%, for example 50 wt.-% to 75 wt.-%, based on the total weight of the curable resin composition.
[0095] In addition to reactive diluent (ii), curable resin composition can include one or more other reactive diluents selected from the following: styrene and styrene derivatives, epoxides, vinyl ethers, acrylates and methacrylates. In this case, reactive diluent (ii) acts as a solubility enhancer. Styrene derivatives include 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene and α-methylstyrene. Suitable acrylates include methyl methacrylate, tert-butyl acrylate, cyclohexyl acrylate, 4-tert-butyl-cyclohexyl acrylate, dimethyl itaconate (DMI), methyl cinnamate, ethyl cinnamate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl methacrylate, isobornyl acrylate, isobornyl methacrylate, 1,4-butanediol dimethacrylate (1,4-BDDMA), triethylene glycol dimethacrylate, trimethylolpropane trimethacrylate and acetoacetoxyethyl methacrylate (AAEMA). Suitable vinyl ethers include cyclohexyl vinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, cyclohexane-1,4-dimethanol divinyl ether and 1,4-butanediol divinyl ether. Suitable epoxides include 2,2-bis[4-(glycidyloxy)phenyl]propane, bis-[4-(glycidyloxy)-phenyl]methane and 1,4-bis(2,3-epoxypropoxy)butane.
[0096] In order to achieve high solubility of the ethylenically unsaturated resin (i), the reactive diluent (ii) is present in an amount of at least 0.5 wt.-%, preferably at least 5 wt.-%, more preferably at least 10 wt.-%, such as at least 25 wt.-%, at least 40 wt.-%, at least 50 wt.-%, at least 60 wt.-% or at least 75 wt.-%, relative to the total amount of reactive diluent (ii) and the further reactive diluent.
[0097] Preferably, the weight ratio of the ethylenically unsaturated resin (i) to the total amount of reactive diluent in the curable resin composition is in the range of 15:85 to 85:15, more preferably in the range of 25:75 to 75:25, especially 30:70 to 70:30 or 30:70 to 60:40.
[0098] In one embodiment, the ethylenically unsaturated polyester resin composition does not include additional reactive diluents.
[0099] In an embodiment the composite glass fiber material comprises the thermosetting polymer in an amount ranging from 10% wt.-% to 90% wt.-%, preferably from 15% wt.-% to 85% wt.-%, more preferably from 20% wt.-% to 80% wt.-%, based on the total weight of the material.
[0100] Composite glass fiber materials include glass fibers. Fibers enhance the mechanical properties and mechanical stability of composite glass fiber materials. Glass fibers are materials composed of many extremely fine glass fibers, and are formed by extruding thin glass filaments (such as silicon-based glass). It has been found that, compared with known reactive diluents (such as styrene), using N-vinyl oxazolidinones with formula (I) as reactive diluents for obtaining composite glass fiber materials increases the impact strength of these materials.
[0101] For every 100 parts by weight of the total amount of ethylenically unsaturated resin (i) and reactive diluent, preferably 10 to 220 parts by weight of glass fibers, more preferably 15 to 200 parts by weight of glass fibers, most preferably 25 to 180 parts by weight of glass fibers are present. The amount of glass fibers within this range allows for the achievement of useful physical properties of the composite glass fiber material.
[0102] In addition to glass fibers, the material may comprise fibers selected from the group consisting of carbon fibers, ceramic fibers, aramid fibers, boron fibers, basalt fibers, steel fibers, natural fibers and / or nylon fibers.
[0103] For every 100 parts by weight of the total amount of ethylenically unsaturated resin (i) and reactive diluent, preferably 10 to 220 parts by weight of fibers, more preferably 15 to 200 parts by weight of fibers, most preferably 25 to 180 parts by weight of fibers are present.
[0104] Glass fibers, as well as the optional additional fibers discussed above, can be characterized by their aspect ratio. Fibers are understood to be materials having an aspect ratio of at least 10, particularly at least 20, more particularly at least 50 or at least 100, and also include fibers modified, for example, by spinning. In a preferred embodiment, the fibers have an aspect ratio in the range of 20 to 100,000, preferably 50 to 100,000, most preferably 100 to 100,000. The length and diameter of the fibers can be determined by a suitable microscope.
[0105] The length of suitable glass fibers is typically in the range of 1 mm to 1 m, preferably 2 mm to 1 m, most preferably 3 mm to 1 m. The diameter of suitable glass fibers is typically in the range of 6 to 25 μm, preferably 10 to 25 μm, most preferably 12 to 25 μm.
[0106] The glass fibers may be present in the material as individual glass fibers, as a web, a fabric (including knitted and woven fabrics, non-crimped fabrics), a scrim, a roving, and the like.
[0107] The composition may contain additional components including stabilizers; inhibitors; pigments and dyes; fillers; thickeners; flame retardants; biocides; thermoplastic shrinkage control agents; toughening agents; curing agents; waxes and other film formers; lubricants; mold release agents; wetting agents; degassing agents; and / or coupling agents.
[0108] In particular, the composition may contain at least one stabilizer or a mixture of stabilizers. Suitable stabilizers include nitroxyl compounds, such as 1-oxyl-2,2,6,6-tetramethylpiperidine or 4-hydroxy-1-oxyl-2,2,6,6-tetramethylpiperidine. In addition, phenol derivatives having at least one substituent in the alpha position of the phenol group are suitable, such as 2,6-di-tert-butyl-4-methylphenol, 1330 or 3114, and tocopherol. Other suitable stabilizers include aromatic amines and phenylenediamines, hindered amines (such as 356. 765, and 770), imines, sulfonamides, oximes, hydroxylamines, urea derivatives, phosphorus-containing compounds, sulfur-containing compounds (such as phenothiazines), complexing agents based on tetraazaannulene (TAA) and / or metal salts. Phosphorus-containing compounds are, for example, triphenylphosphine, triphenyl phosphite, hypophosphorous acid, phosphorous acid, trinonyl phosphite, triethyl phosphite and diphenylisopropylphosphine.
[0109] Suitably, the ethylenically unsaturated resin composition comprises a total amount of stabilizer in the range of 0.01 to 5 wt.-%, preferably 0.02 to 3 wt.-%, more preferably 0.025 to 2.5 wt.-%, relative to the total amount of the ethylenically unsaturated resin composition.
[0110] Suitable inhibitors include hydroquinone, 2-methylhydroquinone, 2-tert-butyl-hydroquinone, p-benzoquinone, 2-methyl-p-benzoquinone, 2-tert-butyl-p-benzoquinone, 1,4-naphthoquinone, 4-tert-butyl-catechin (TBC), 1,2-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, N-nitroso-N-phenylhydroxylamine ammonium salt and tris(N-nitroso-N-phenylhydroxyl-aminato)aluminum.
[0111] Suitable pigments and dyes are materials which change the color of reflected or transmitted light due to wavelength-selective absorption. An example of a pigment is titanium dioxide.
[0112] Fillers are inert compounds that increase the volume of the unsaturated polyester resin composition. For every 100 parts by weight of the mixture of unsaturated resin (i) and reactive diluent (ii), preferably 20 to 280 parts by weight of fillers are present in the unsaturated polyester resin composition. An example of a filler is calcium carbonate.
[0113] Thickeners increase the viscosity of the unsaturated polyester resin composition and reduce its tack, thereby improving the handling of the composition. Examples of thickeners are isocyanates such as 4,4'-methylene-diphenyl-diisocyanate, magnesium oxide (MgO), calcium hydroxide (Ca(OH)2), and calcium oxide (CaO).
[0114] Flame retardants are substances that prevent or slow the development of ignition. Suitable flame retardants include solid flame retardants such as aluminum trihydrate (ATH), magnesium hydroxide (Mg(OH)2), and ammonium polyphosphate (APP). Other suitable flame retardants include triphenyl phosphate, resorcinol tetraphenyl diphosphate, bisphenol A tetraphenyl diphosphate, decabromodiphenylethane, ethylene-bis-(tetrabromophthalimide), tris(tribromophenyl)cyanurate and / or dodecachloropentacyclo-octadecadiene (Dechlorane ). In addition, halogenated flame retardants can be combined with synergists like antimony trioxide (Sb2O3) or 2,3-dimethyl-2,3-diphenyl-butane Use in combination.
[0115] Biocides are materials that destroy, prevent, make harmless or apply control effects to any harmful organisms by chemical or biological means. Suitable biocides include materials based on silver, copper or zinc, which are supplied as salts (zinc pyrithione) or oxides or by the zeolite of load or by nanoparticles. Other suitable biocides include chitosan, 10,10'-oxybisphenoxane (OBPA), isothiazolinone, 2,4,4'-trichloro-2'-hydroxy-diphenyl ether (triclosan), N-(fluorodichloro-methylthio) phthalimide, thiabendazole (TBZ) or methylthio-cyclopropylamino-tert-butylamino-s-triazine and synthetic polymer poly-(tert-butylaminoethyl methacrylate), poly-(tert-butylaminomethylstyrene), and active copolymers thereof.
[0116] Thermoplastic shrinkage control agents are substances that can be used in sheet molding compound (SMC) and bulk molding compound (BMC) technology to compensate for shrinkage by forming microvoids in the thermoplastic phase during curing. Suitable thermoplastic shrinkage control agents include solid polymers (such as powdered polyethylene) and liquid solutions in styrene made from thermoplastic polymers such as polystyrene and styrene copolymers, polymethyl methacrylate (PMMA), polyvinyl acetate (PVAc) and functionalized PVAc, saturated (non-curable) polyesters and rubbers.
[0117] Tougheners are used to improve the damage tolerance of cured olefinic unsaturated polyester resin compositions. In particular, elongation at break and impact strength can be enhanced, while crack formation under long-term static and dynamic loads can be reduced. Suitable tougheners include rubber, nanoparticles (i.e., particles with an average diameter less than 1 μm or precursors forming such nanoparticles), thermoplastic polymers different from olefinic unsaturated resins (i), and block copolymers different from olefinic unsaturated resins (i). Tougheners can be present in the resin composition in an amount of 2 wt.% to 40 wt.%, preferably 3 wt.% to 30 wt.%, more preferably 5 wt.% to 25 wt.%, relative to the total amount of the curable resin composition.
[0118] Suitable rubbers include acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (H-NBR), polychloroprene (CR), styrene-butadiene rubber (SBR), natural rubber (NR), polyisobutylene (PIB), ethylene-propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), and rubbers based on polyacrylates, acrylate rubbers (AM) and fluororubbers as well as functionalized rubbers like carboxyl-terminated NBR (CTBN) or epoxy-terminated NBR (ETBN).
[0119] Suitable nanoparticles include soot, carbon black (high wear furnace, ultra high wear furnace), pyrogenic silicic acid, surface modified pyrogenic silicic acid, fumed silica, precipitated silica, rigid phase material from polyurethane recycling, silica particles modified by hydrolysis of functionalized silanes, montmorillonite, bentonite and exfoliated montmorillonite.
[0120] Suitable thermoplastic polymers other than the ethylenically unsaturated resin (i) include polysulfone (PSU), polyethersulfone (PES), polyphenylsulfone (PPSU), polyoxy-2,6-dimethyl-1,4-phenylene (PPE), polycarbonates based on bisphenol A and bisphenol TMC (APEC ), copolymer of styrene and maleic anhydride Styrene, copolymer with maleic anhydride and N-phenylmaleimide Copolymers of styrene and glycidyl methacrylate, copolymers of styrene and acrylonitrile (SAN); copolymers of styrene, butadiene and acrylonitrile (ABS); copolymers of styrene, acrylate monomers and acrylonitrile (ASA); copolymers of acrylonitrile and α-methyl-styrene (AMSAN), amorphous polyamide, polymethacrylimide, polyvinylidene fluoride (PVDF), polyvinyl fluoride (PVF), ethylene-tetrafluoroethylene copolymer (ETFE) and copolymers of tetrafluoroethylene and hexafluoropropylene.
[0121] Suitable block copolymers other than the ethylenically unsaturated polyester resin (i) include styrene-butadiene-styrene block copolymers (SBS), polyetheramide block copolymers, polyetherester block copolymers, thermoplastic polyurethanes (TPU) based on polyesters, polyethers and polycarbonates.
[0122] A curing agent is a compound or mixture of compounds that accelerates the curing process.
[0123] When curing is carried out at a temperature between 5°C and 45°C, it may be referred to as a "cold cure." Cold curing may be carried out via a combination of benzoyl peroxide with an amine accelerator; or via a combination of a hydroperoxide with a metal accelerator.
[0124] Suitable benzoyl peroxides include dibenzoyl peroxide and 4,4'-dichloro-dibenzoyl peroxide. Suitable amine accelerators include N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyltoluidine, N,N-diethyltoluidine, N,N-bis(2-hydroxyethyl)aniline, N,N-bis(2-hydroxyethyl)-toluidine, N,N-bis(2-hydroxypropyl)-aniline, and / or N,N-bis(2-hydroxypropyl)toluidine.
[0125] Suitable hydroperoxides include hydrogen peroxide, tert-butyl hydroperoxide, tert-amyl hydroperoxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, acetylacetone peroxide, trimethylcyclohexanone peroxide, isobutyl methyl ketone peroxide. Suitable metal promoters include organic salts of Co(II), Mn(II), Cu(I), Cu(II) or Fe(II), such as metal salts of ethylhexanoic acid or cyclohexane acid.
[0126] When curing is carried out at a temperature above 45°C and 120°C, it may be referred to as "thermal curing". Thermal curing may be carried out using one or more thermal initiators as curing agents. Suitable thermal initiators include peroxides, azo compounds and CC labile compounds.
[0127] Suitable peroxides include methyl ethyl ketone peroxide, 2,4-pentanedione peroxide, methyl isobutyl ketone peroxide, cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl peroxyneodecanoate, 2,5-dimethyl-2,5-di-(2-ethyl-hexanoylperoxy)hexane, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy tert-Butyl-2-methylbenzoate, tert-butyl peroxycarbonate 2-ethylhexyl, tert-butyl peroxycarbonate isopropyl, tert-amyl peroxybenzoate, tert-butyl peroxybenzoate, 1,1-di-(tert-amyl peroxy)cyclohexane, 1,1-di-(tert-butyl peroxy)-3,3,5-trimethyl-cyclohexane, 1,1-di-(tert-butyl peroxy)-cyclohexane, 2,2-di-(tert-amyl peroxy)butane, 4,4-di- -Butyl (tert-butyl peroxy) valerate, dilauroyl peroxide, di-(2-tert-butyl peroxyisopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di-(tert-butyl peroxy)hexane, di-tert-butyl peroxide, di-tert-amyl peroxide, dicumyl peroxide, di(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-di-(tert-butyl peroxy)hexane, tert-butyl cumyl peroxide The compounds include 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3,3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxycyclononane, di-(4-tert-butylcyclohexyl) peroxydicarbonate, di-(2-ethylhexyl) peroxydicarbonate, tert-butyl hydroperoxide, cumyl hydroperoxide, isopropylcumyl hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.
[0128] Suitable azo compounds include 2,2'-azobis(2-isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile) and 1,1'-azobis(hexahydrobenzonitrile).
[0129] Suitable CC labile compounds include 2,3-dimethyl-2,3-diphenylbutane and 3,4-dimethyl-3,4-diphenylhexane.
[0130] Other suitable curing agents include compounds that generate free radicals when irradiated with UV-A light (i.e., light with a wavelength of 315 to 380 nm). Such curing agents may be referred to as photoinitiators. Suitable photoinitiators include benzoin, benzil, α-hydroxy ketones, α-amino ketones, acylphosphine oxides, bisacylphosphine oxides, or combinations thereof. Preferred photoinitiators include 369, 651, 184. 819, 907 and TPO.
[0131] In one embodiment, the curable resin composition does not include a curing agent.
[0132] The composite glass fiber material can be obtained by curing the curable resin composition. In a preferred embodiment, curing is carried out by free radical polymerization via a curing agent. Suitable curing agents are as described above. Alternatively, curing can be carried out in the absence of a curing agent.
[0133] Curing can be carried out with the aid of high-energy radiation. Examples of high-energy radiation suitable for curing are electron radiation, or α-, β- or γ-radiation, preferably γ-radiation.
[0134] Curing of the unsaturated ethylenically unsaturated polyester resin composition is preferably carried out at elevated temperatures, preferably in the range of 120° C. to 250° C. The temperature may be increased stepwise during the curing process.
[0135] In a preferred embodiment, the curing of the unsaturated polyester resin composition is performed at a temperature ranging from 15° C. to 50° C. for 2 to 200 hours and thereafter at 80° C. to 120° C. for 2 to 24 hours.
[0136] In one embodiment, the cured unsaturated polyester resin composition is further subjected to a post-curing process. The duration of the post-curing is preferably 1 to 12 hours. The post-curing is preferably carried out at a temperature of 80°C to 200°C, in particular 80°C to 150°C.
[0137] The composite glass fiber material according to the present invention can be used to produce storage tanks, polymer concrete, artificial stone, device construction, medical equipment, railway equipment, oil and gas field equipment, automobile body parts, truck body parts, headlight reflectors, gel coatings, top coatings, protective layers and other coating applications (such as spraying, in-mold coating and painting), putties, cast products, buttons, porous materials (such as foams, films, etc.), for the production of fibers, for the production of tools, electronic devices, flame retardant thermoset materials, profiles, containers, moldings, polymer parts, long field lamp stands, oil tanks, sheets / boards, railway interior components, adhesives and pipes.
[0138] Furthermore, the present invention provides a method for producing a composite glass fiber material, the method comprising contacting glass fibers with a curable resin composition comprising:
[0139] (i) ethylenically unsaturated resins; and
[0140] (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I)
[0141]
[0142] Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms;
[0143] wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-% relative to the total amount of reactive diluent (ii) and the further reactive diluent;
[0144] and curing the curable resin composition to form a thermosetting polymer, thereby obtaining a composite glass fiber material.
[0145] The above discussion and examples regarding the composite glass fiber materials of the present invention should be understood to be equally applicable to the methods of the present invention.
[0146] As used herein, the term "contacting" should be understood broadly and includes all measures that result in a material in which glass fibers are present in a matrix of a cured resin composition. This includes mixing glass fibers with a curable resin composition, impregnating a knitted or woven fabric of glass fibers with a curable resin composition, impregnating glass fiber rovings with a curable resin composition, and the like.
[0147] Furthermore, the present invention provides the use of N-vinyl oxazolidinone having the formula (I) in a method for obtaining a composite glass fiber material
[0148]
[0149] Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms.
[0150] In one embodiment, a curable resin composition comprising:
[0151] (i) an ethylenically unsaturated resin as defined above; and
[0152] (ii) a reactive diluent which is an N-vinyloxazolidinone having formula (I) as defined above;
[0153] Wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-%, relative to the total amount of reactive diluent (ii) and the further reactive diluent.
[0154] The above discussion and examples concerning the composite glass fiber material of the present invention should be understood to be equally applicable to the use of the present invention.
[0155] In addition, the present invention provides a curable resin composition comprising
[0156] (i) ethylenically unsaturated resins; and
[0157] (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I)
[0158]
[0159] Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms;
[0160] wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-% relative to the total amount of reactive diluent (ii) and the further reactive diluent;
[0161] And wherein the ethylenically unsaturated resin (i) is selected from ethylenically unsaturated polyester resins, vinyl ester resins, and combinations thereof.
[0162] The above discussion and examples regarding the composite glass fiber materials of the present invention should be understood to be equally applicable to the curable resin compositions of the present invention.
[0163] The curable resin composition as described above can be used as a matrix polymer for reinforced and non-reinforced thermosetting materials in the following: SMC technology (sheet molding composite technology), BMC technology (bulk molding technology), resin transfer molding (RTM), compression molding, hot molding, FCS technology (fiber composite spray technology), injection molding, vacuum assisted resin infusion, continuous sheet production, filament winding, rotational molding, lamination, vacuum pressure impregnation (VPI process), pultrusion, casting, bundling, bonding, gel coating, top coating, spraying, filling, in-mold coating, doctor blade coating, dip coating, drip coating, painting, line painting (enamel coating) and other coatings, fiber spinning and foaming.
[0164] The present invention is described in further detail by the following examples.
[0165] Examples
[0166] The ethylenically unsaturated resin is obtained as described below.
[0167] The following table provides a summary of the reactants, stabilizers, and initiators used in the working examples.
[0168]
[0169]
[0170] A-1. Production of ethylenically unsaturated polyester resins
[0171] The ethylenically unsaturated polyester resin is obtained by reacting the compounds specified in the following table in the specified molar ratios. The ethylenically unsaturated polyester resin is prepared by melt polycondensation.
[0172] A four-necked flask (2L) is provided. In the middle neck, an agitator with a single blade is installed. The bearing housing of the agitator is continuously cooled with water. On the other three necks, a thermocouple, an insulation filling column and a plug are provided. A distillation bridge with a ground joint thermometer is installed on the column to monitor the head temperature of the system during polycondensation. A graduated cylinder (250mL) is attached to the distillation bridge to collect and measure the amount of condensed water. Thermocouple is connected to Julabo laboratory controller (PID) and the reactor temperature is controlled via a computer program (JULABO EasyTemp Professional). A heating jacket (which is also controlled by Julabo laboratory controller) is used as a heating source.
[0173] At the beginning of the reaction, 500 ppmw of hydroquinone was added relative to the total reaction mixture as a free radical scavenger. At the beginning of the reaction, 400 ppmw of Fascat 4100 (butyl stannoic acid) was added relative to the total reaction mixture as an esterification catalyst. The reaction was carried out in a four-necked flask (2 L) with a stirrer and a thermometer as described above under a nitrogen atmosphere (99.999% nitrogen).
[0174] Heating from room temperature to 80°C is carried out as quickly as possible by program control while avoiding overheating. At 80°C, the maleic anhydride ring opens and an exothermic reaction occurs. The heating is turned off in order not to overheat the melt. After the exothermic reaction is complete, the temperature is further increased to as high as 110°C. Subsequently, the reaction temperature is increased by 10°C per hour until 190°C. At 135°C to 145°C, the formation of water is first observed. As soon as the melt of the unsaturated polyester reaches 190°C, the reaction is stopped. The polymer is cooled and left overnight in its solid form.
[0175] Subsequently, the polymer is melted again by heating to 190° C. Reaction is carried out until the desired acid number is obtained. For the polyester with phthalic anhydride, the melt is cooled to 155° C. and stirred for one hour. Subsequently, the unsaturated polyester is poured into a shallow rectangular mold, where it is allowed to cool and solidify.
[0176] The acid number (neutralization number) is the mass of potassium hydroxide (KOH) in milligrams required to neutralize one gram of ethylenically unsaturated resin. The acid number indicates the number of carboxylic acid groups per gram of compound and is determined in accordance with DIN EN ISO 2114 via titration.
[0177] The hydroxyl number is the amount of potassium hydroxide (KOH) in milligrams required to neutralize the acetic acid absorbed when one gram of a chemical substance containing free hydroxyl groups is acetylated. The hydroxyl number indicates the number of free hydroxyl groups per gram of a compound and is determined by titration in accordance with DIN EN ISO 4692-2.
[0178] The vinyl density indicates the molar proportion of vinyl groups per kg of resin. The vinyl density is determined by nuclear magnetic resonance (NMR) spectroscopy.
[0179] Glass transition temperature T of ethylenically unsaturated polyester resin g The DSC measurement was performed using a DSC device Sirius 3500 from Netzsch. Hermetically sealed Tzero aluminum pans were used. For the DSC measurement, about 15 mg of unsaturated polyester resin were added to the Tzero pan. The Tzero cover was then placed on the pan and sealed with the help of a press, the pan was inserted into the DSC and the measurement was started.
[0180] In the first heating cycle, the disk was first cooled to 0° C. and then heated to 100° C. at 10 K / min. In the second heating cycle, the disk was cooled to −80° C. and then heated to 100° C. at 10 K / min. Determination of T from the second heating cycle g .
[0181] Mass average molecular weight M w and number average molecular weight M n The polydispersity index Q is calculated as M w / M n .
[0182] In particular, analytical columns from PSS Polymer Standard Solutions were used as separation columns. The stationary phase consisted of a 3 μm particle size and a nominal pore size of The separation column was thermoregulated to 35°C in a column oven. At a sample concentration of 4.94 g / L, the injected sample volume was 50 μL, which in sample preparation corresponds to 50 mg sample to 9 g eluent. The flow rate of the eluent was 0.5 mL / min. The samples were detected with a refractive index detector and a UV-VIS detector, with the measurement signals being recorded once per second. Two GPC measurement series were performed for each polyester. The chromatograms were evaluated using the PSS WinGPC UniChrom software. Calibration was performed with appropriate standard kits for styrene oligomers and polymers.
[0183] Melt viscosity was determined at 100° C. or 150° C. via an ICI-cone and plate viscometer from Epprecht Control & Instrument (FIC) according to the following table. A standard cone C ( The measurement was carried out with a cone angle of 0.5°. About 0.5 g of solid unsaturated polyester resin was used for the measurement.
[0184] The table below shows the composition and properties of unsaturated resins.
[0185]
[0186] 1 AV = Acid Value 2 EGD = vinyl density 3 Q = polydispersity index
[0187] 4 T V = Temperature at which viscosity measurement is performed 5 η = viscosity
[0188] B. Prediction of Hansen Solubility Parameters for Unsaturated Resins
[0189] The Hansen parameters of unsaturated resins are predicted based on the corresponding oligomers using the software COSMOquick 2021. First, the molecules are drawn as 12-mer oligomers in the included JChemPaint module. Then, the corresponding SMILES strings are generated. Finally, the quantitative structure-activity relationship (QSPR) model is used to obtain the Hansen solubility parameters. The QSPR results are fitted to the published empirical Hansen values ("Hansen Solubility Parameters: A User's Handbook", C.M. Hansen, 2007, 2nd edition, CRC Press). The results are shown in the table below.
[0190]
[0191] C. Curable Resin Composition
[0192] C-1. Production of curable resin composition
[0193] The cured ethylenically unsaturated resin obtained according to item A-1 is crushed using a hammer. If the unsaturated resins do not solidify at room temperature, they are cooled with liquid nitrogen and then crushed in a cold state. According to the following table, the crushed resin is used to produce a curable resin composition. First, the unsaturated resin particles are weighed into a glass bottle. Subsequently, a reactive diluent or a reactive diluent mixture according to the following table is added. 765 (1,000ppmw) added to The unsaturated resin particles are completely dissolved in the reactive diluent or reactive diluent mixture, and the curable resin composition is considered ready for use.
[0194] C-2. Solubility
[0195] The bottles obtained according to item C-1 were placed on a roller mixer and mixed for several days. The bottles obtained according to item C-1, wherein the curable resin composition comprises cyclohexyl vinyl ether, were subsequently placed in an oven at 60° C. for 3 h. The solubility of the ethylenically unsaturated resin particles in the reactive diluent was visually checked at regular intervals.
[0196] The results of the solubility testing are shown in the table below.
[0197]
[0198]
[0199] A turbid solution indicates that dissolution has not been completely achieved. The unsaturated resin being examined is completely dissolved.
[0200] C-3. Surface adhesion and curing characteristics
[0201] The surface of unsaturated polyester thermosets made from resins with acrylates as reactive diluents may become tacky after curing in air. The tackiness of the thermoset surface is caused by oxygen inhibition during the free radical curing process. The viscosity of the curable resin composition obtained with the thermosetting polymer was compared.
[0202] As indicated in the table below, unsaturated polyester resins 1-2 were dissolved in 60 wt.-% tert-butyl acrylate or to obtain curable resin compositions. 1 wt.-% of Trigonox 21 was added to each curable resin composition. The curable resin compositions were cured using the following curing profile: 2 h at 60° C., then 2 h at 80° C., then 2 h at 100° C. The results are shown in the following table.
[0203]
[0204] *1000ppmw 765 (relative to the total amount of the curable resin composition) and Added together to improve storage stability.
[0205] Both curable resin compositions can be cured to produce a thermosetting polymer having a smooth surface, wherein the The thermosetting polymer obtained from the curable resin composition does not show surface stickiness. It should be noted that despite the presence 765 (which can act as an inhibitor during the curing process), but contains The resin composition still achieves this effect.
[0206] In addition, the curing characteristics of the unsaturated resins 1-1 to 1-4 in 1,4-butanediol diacrylate were examined. The corresponding unsaturated resins were dissolved in 60 wt.-% of 1,4-butanediol diacrylate to obtain curable resin compositions. 1 wt.-% of Trigonox 21 was added to each curable resin composition. The curable resin compositions were cured using the following curing profile: 2 h at 60° C., then 2 h at 80° C., then 2 h at 100° C., to obtain thermosetting polymers.
[0207] Each resin with 1,4-butanediol diacrylate as reactive diluent was found to foam during thermal curing under air.The surface of the obtained thermosetting polymer was uneven and rough and its quality was not sufficient for further investigation.
[0208] C-4. Glass transition temperature T g
[0209] The glass transition temperatures of thermosetting polymers obtained from curable resin compositions comprising different reactive diluents according to the table below are compared. The curable resin compositions each comprised 1 wt.-% of tert-butyl peroxybenzoate. The curable resin compositions were cured using the following curing profile to obtain thermosetting polymers: A) 2 h at 60° C., then 2 h at 80° C., then 2 h at 100° C.; or B) 1 h at 80° C., then 1 h at 160° C. The results are shown in the table below.
[0210]
[0211] It is obvious that compared with using 1,4-butanediol dimethacrylate or triethylene glycol dimethacrylate as reactive diluent, As a reactive diluent, the glass transition temperature of the thermosetting polymer obtained with resins 1-3 is at least 40°C higher. In addition, it is clear that As a reactive diluent it leads at high concentrations to high glass transition temperatures which cannot be obtained with 4-methylstyrene or divinylbenzene since these reactive diluents have solubility problems at comparably high concentrations.
[0212] C-5. Cold curing
[0213] For cold curing according to the following table The properties of the thermosetting polymers obtained from the curable resin compositions with 1,4-butanediol dimethacrylate (1,4-BDDMA) as reactive diluents were compared. Acetoacetoxyethyl methacrylate (AAEMA) and dimethyl itaconate (DMI) were used as additional reactive diluents. Before curing, 1.5 wt.-% of a cobalt accelerator ( Co 1) was added to the curable resin composition and the composition was homogenized in a roller mixer for 1 h. Subsequently, 1.5 wt.-% of methyl ethyl ketone peroxide (MEKP) was added and mixed with the curable resin composition using a wooden spatula. The curable resin composition was processed immediately after the addition of MEKP.
[0214] About 10 g of resin was placed on a metal mold (size: 10 cm x 10 cm). The resin was evenly distributed and a biaxial glass fiber fabric layer (831 g / m 2 , 0° / 90°, product number S14EB490-00831-01300-474000, from Saertex, size: 10 cm×10 cm) is placed in the resin. Once all bubbles are removed using a wooden scraper, a second layer of resin is added. A second layer of glass fiber fabric is placed at an angle of 90° to the first layer and is also wetted with resin. The process is repeated again so that the metal tray contains three layers of glass fiber at 90° to each other and about 30 g of the resin composition.
[0215] Cold curing was carried out at a temperature of approximately 25° C. The tack of the resulting samples was controlled tactilely at regular intervals of about 6 h during the day.
[0216] The results are shown in the table below.
[0217]
[0218] * with 45 wt.-% unsaturated resin
[0219] Obviously, it contains The cold curing of the resin with BDDMA as a reactive diluent proceeds faster than the cold curing of the resin containing 1,4-BDDMA as a reactive diluent.
[0220] C-6. Curable resin composition with additional reactive diluent
[0221] According to Project A-1, a mixture of fumaric acid and 2-methyl-2-propylpropane-1,3-diol (molar ratio 1.0:1.02, δ p =5.702MPa 1 / 2 ) obtained from an ethylenically unsaturated polyester resin. The unsaturated resin was cooled with liquid nitrogen and then crushed in a cold state. The crushed unsaturated resin was used to produce a curable resin composition. First, the unsaturated resin particles were weighed into a glass bottle. Subsequently, styrene and and a mixture of stabilizers.
[0222] The bottle was placed on a roller mixer. The solubility of the unsaturated polyester particles in the reactive diluent or the progress of the dissolution process was visually checked at regular intervals. Once everything was dissolved, the resin composition was considered ready for use.
[0223] The results of the solubility tests are shown in the table below. The Hansen solubility parameters of the mixture are converted from mass fraction to volume fraction using the following formula:
[0224]
[0225] in is the volume fraction of component 1, ω1 is the mass fraction of component 1, ω2 is the mass fraction of component 2, ρ1 is the density of component 1 and ρ2 is the density of component 2. The density of styrene is 0.909 kg / m 3 . The density is 1.098kg / m 3 .
[0226] Use styrene and The Hansen solubility parameter of the mixture is compared with the Hansen solubility parameter of the unsaturated polyester resin to determine R according to the following formula a value:
[0227]
[0228]
[0229]
[0230] It is clear that even small amounts of The presence of improves the solubility of the polyester resins examined.
[0231] C-7. Tensile test
[0232] The curable resin composition prepared according to C-1 was used to prepare the samples for tensile testing. Before sample preparation, 0.3 wt.-% of 819 and 1 wt.-% of tert-butyl peroxybenzoate (TBPB) were added to the curable resin composition. The samples for tensile testing were prepared by vacuum infusion method.
[0233] For this purpose, a sealing tape was applied to a glass plate (28×17 cm) and two parallel opposing spiral hoses were arranged in length. The spiral hoses were firmly pressed onto the sealing tape to avoid possible leaks. A vacuum hose was inserted into each spiral hose to a depth of about 3 cm. The vacuum hoses were covered and sealed by a small piece of sealing tape. This construction represented the framework for vacuum infusion.
[0234] Subsequently, six layers of glass fiber fabric (24×13 cm, 831 g / m 2 , 0° / 90°, product number S14EB490-00831-01300-474000, from Sartex) is placed on a glass plate. The layers are arranged alternately at an angle of 45°. A release film (peel layer 64 g / m 2 The test specimens were tested using a 150 cm (plain weave) laminate (INFUPLEX with ISONET, width 145 cm, product number 3903426). The release film provided a smooth surface for the test specimen. The resin ooze layer consisted of a two-layer system: perforated flow and flow assist. The system was permeable to the resin and allowed uniform and complete wetting of the laminate by fine commercial structures. Finally, the mold was securely sealed with a vacuum foil.
[0235] The curable resin composition is degassed by a vacuum pump before the infusion process. For infusion, a shorter vacuum hose is placed in the resin and a longer vacuum hose is connected to the vacuum circuit. The device consists of a vacuum pump, a dryer and an insertable cold trap. The dryer includes a collection container for excess flowing resin. The board should be produced in a dark place to avoid possible premature curing. Once the board is finally laminated, the vacuum hose is compressed with the aid of a clamp and then cut off. Next, the board is photochemically cured for 20 min in a xenon tester (Original Hanau, serial number 7011, overall dimensions 700×470×350mm, power supply: 220V / 50Hz / 1500W). The laminate is carefully removed from the glass plate and post-cured for 1 hour at 80°C and 1 hour at 160°C in a convection oven to obtain a thermosetting material. The sample is cut into four equal-sized test specimens of 200mm length and 25mm width on a CNC machine.
[0236] To evaluate the mechanical properties, tensile tests were performed on a Zwick Z200 according to DIN EN ISO 527-4. For each test, four test specimens of equal size were used. The width and thickness of all specimens were measured with a caliper and the corresponding tests were recorded. Each thermosetting material obtained from the curable resin composition was tested at room temperature (about 20°C), 100°C and 120°C. For the measurements at 100°C and 120°C, the climate chamber was connected to the Zwick Z200 and preheated for at least one hour. Before the measurement started, the sample was heated and clamped in the Zwick Z200 for 10 minutes. It is important to ensure that no shear forces are generated when clamping the test specimen. This means that the specimen must be mounted vertically in the clamp. The airflow generated by the oven fan must be turned off for the duration of the measurement. The Zwick Z200 loads the sample until it finally breaks. The tensile modulus of elasticity (E t ), tensile strength (σ m ) and the elongation at maximum tensile stress (ε m ).
[0237] The results of the measurements are shown in the following table.
[0238]
[0239] All thermosetting materials obtained from the curable resin compositions showed adequate mechanical properties. Compared with itself, it was found that the use of dimethyl itaconate (DMI) as an additional reactive diluent improved the mechanical properties. Without wishing to be bound by theory, DMI can also serve as a copolymerization partner of VMOX in addition to unsaturated polyester resins 1-3. Therefore, free radical copolymerization can occur between the unsaturated polyester resin and VMOX, as well as between DMI and VMOX. The copolymerization between VMOX and DMI increases the possibility of forming reactive diluent bridges between the chains of the unsaturated polyester resin, thereby increasing the crosslinking density and uniformity of the network.
[0240] D. Composite fiberglass materials
[0241] D-1. Dynamic mechanical analysis
[0242] Use of item C-1 containing 70 wt.-% Glass fiber reinforced test specimens were prepared from a resin composition of 100 g / cm2. As a first step, tert-butyl peroxybenzoate (Acros Organic Reagents, 98%) was added to the resin in an amount of 1 wt.-%. Then, approximately 10 g of the resin was placed in a metal pan (diameter: 10 cm; depth: 1 cm). The resin was evenly distributed and a biaxial glass fiber fabric layer (831 g / m 2) of the same diameter was placed on the glass fiber layer. 2 , 0 ° / 90 °, product number S14EB490-00831-01300-474000, from Saertex (Saertex)) is placed in the resin. Once all bubbles are removed using a wooden scraper, a second layer of resin is added. The second glass fiber fabric layer is placed at a 90 ° angle to the first layer and is also wetted with resin. The process is repeated again so that the metal tray contains three layers of glass fibers at 90 ° to each other and about 30 g of the resin composition.
[0243] The obtained sample was pressed with a weight (about 500 grams) wrapped in aluminum foil to squeeze the excess resin composition out of the mold and obtain a smooth sample surface. Finally, the sample and the weight were wrapped in aluminum foil. The sample was thermally cured at 100°C for 1 h and at 160°C for 1 h in a laboratory oven under air. After cooling, the obtained composite glass fiber material was removed from the mold and cut into 10×50 mm samples using a table saw.
[0244] Subsequently, the samples were subjected to dynamic mechanical analysis (DMA) using a DMA 242C from NETZSCH. A three-point bending specimen holder was used. The samples were measured under a nitrogen flow of 83 mL / min according to the methods specified in the table below. The temperature dependence of the storage modulus, loss modulus and loss factor (tan δ) of the cured ethylenically unsaturated polyester resin composition was determined. The maximum value of the tan δ curve (T) is considered to constitute the glass transition temperature T g .
[0245]
[0246] Glass transition temperature T of composite glass fiber materials g Shown in the table below.
[0247]
[0248] D-2. Impact test
[0249] Composite test specimens were made using resin compositions derived from unsaturated resins 1-3 according to item C-1, these resin compositions comprising 60 wt.-% of or styrene. Add 765 (1,000 ppmw) was used as a stabilizer to inhibit gelation. Chopped glass fibers (HP-GS3, HP-Textiles) with a fiber length of 3 mm and a diameter of 13 μm (aspect ratio: 231) or talc (fine powder Mg3[(OH)2|Si4O 10 ], 30-0050). The density of the two materials is roughly the same, i.e. 2.4 to 2.8 g / cm 3 .
[0250] The cobalt accelerator ( Co 1, Bufa Chemical Company) was added to 400 g of each curable resin composition. Subsequently, methyl ethyl ketone peroxide (MEKP, United Initiators) was added and mixed with the curable resin composition using a wooden spatula. For the curable resin composition containing styrene, 1.25 wt.-% of each of the cobalt accelerator and MEKP was used. For the curable resin composition containing A curable resin composition using 0.5 wt.-% each of a cobalt accelerator and MEKP.
[0251] Finally, add 10wt.-% of chopped glass fiber or talcum as described above and mix in curable resin composition at 750rpm for 120s.After mixing, each curable resin composition is divided into three metal plates (diameter: 100cm) so that the resin is evenly distributed, and each plate is filled to a height of 10 to 12mm.Use a desiccant under 10 mbar pressure to remove bubbles from the composition during cold curing at room temperature.After the cold curing of the composition is completed (about 1h), the sample is heat cured at 80°C for 8h.
[0252] The cured composite test specimens were removed from the metal trays and cut to size on a CNC cutting machine. For each composite material, test bars with a width of approximately 8 mm, a height of approximately 4 mm and a length of approximately 80 mm were obtained.
[0253] The impact test was carried out with an impact tester from Zwick. The impact pendulum had an energy of 0.5 joules. Prior to the impact test, the width and height of each test bar were determined using a caliper gauge. The test specimen was placed in the impact tester so that the impact pendulum struck centrally one of the narrow sides, i.e. one of the face sides whose area can be defined as length × height.
[0254] Use the following formula to determine impact strength:
[0255]
[0256] where a C U is the impact strength (in kJ / m 2 W C is the impact energy (in J), h is the height of the specimen, and b is the width of the specimen. The results are shown in the following table.
[0257] Table D-2-1: Derived from and talc composite samples.
[0258]
[0259] Table D-2-2: Derived from and glass fiber composite specimens.
[0260]
[0261]
[0262] Table D-2-3: Composite specimens derived from styrene and glass fibers.
[0263]
[0264] Table D-2-4: Summary of impact strength tests
[0265]
[0266] It is obvious that the composite material derived from glass fiber has a higher impact strength than the composite material based on talc. In addition, it is obvious that the composite glass fiber material derived from N-vinyl oxazolidinone with formula (I) has a higher impact strength than the composite glass fiber material based on styrene. In addition, N-vinyl oxazolidinone with formula (I) requires less initiator for cold curing than styrene.
Claims
1. A composite glass fiber material comprising a thermosetting polymer, wherein the thermosetting polymer is obtained from a curable resin composition comprising: (i) ethylenically unsaturated resins; and (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I) Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms; Wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-%, relative to the total amount of reactive diluent (ii) and the further reactive diluent.
2. The material according to claim 1, wherein -R 1 , R 2 , R 3 and R 4 At least two of 1 , R 2 , R 3 and R 4 each of which is a hydrogen atom; or -R 1 is a C1-C4 alkyl group and R 2 , R 3 and R 4 is a hydrogen atom; or -R 4 is a C1-C4 alkyl group and R 1 , R 2 and R 3 is a hydrogen atom; or -R 1 and R 2 is a hydrogen atom and R 3 and R 4 It is a C1-C4 alkyl group.
3. A material according to any one of the preceding claims, wherein The N-vinyloxazolidinone of formula (I) is 3-vinyloxazolidin-2-one, 4-methyl-3-vinyl-oxazolidin-2-one, or 5-methyl-3-vinyl-oxazolidin-2-one, in particular 5-methyl-3-vinyl-oxazolidin-2-one.
4. A material according to any one of the preceding claims, wherein The ethylenically unsaturated resin (i) is selected from the group consisting of ethylenically unsaturated polyester resins, vinyl ester resins, and urethane (meth)acrylate resins.
5. A material according to any one of the preceding claims, wherein The weight ratio of the ethylenically unsaturated resin (i) to the total amount of reactive diluent in the curable resin composition is in the range of 15:85 to 85:15, more preferably in the range of 25:75 to 75:25, especially 30:70 to 70:30 or 30:70 to 60:
40.
6. A material according to any one of the preceding claims, wherein The ethylenically unsaturated resin (i) has at least one of the following characteristics: - a number average molecular weight in the range of 500 to 10,000 g / mol as determined by gel permeation chromatography; - an acid number in the range of 5 to 80 mg KOH / g, as determined by titration in accordance with DIN EN ISO 2114; as well as - a hydroxyl number in the range from 5 to 80 mg KOH / g, as determined by titration in accordance with DIN EN ISO 4692-2.
7. A material according to any one of the preceding claims, wherein The ethylenically unsaturated resin (i) has a vinyl density in the range of 0.5 to 10 mol / kg, in particular - when the ethylenically unsaturated resin (i) is an ethylenically unsaturated polyester resin, in the range of 2.0 to 9.0 mol / kg; - when the ethylenically unsaturated resin (i) is a vinyl ester resin, in the range of 1.0 to 4.5 mol / kg; - when the ethylenically unsaturated resin (i) is a urethane (meth)acrylate resin, in the range of 1.0 to 5.0 mol / kg; Herein the vinyl density represents the molar proportion of vinyl groups per kg of resin, as determined by nuclear magnetic resonance spectroscopy.
8. A material according to any one of the preceding claims, wherein The curable resin composition preferably comprises the ethylenically unsaturated resin (i) in an amount of 15 to 85 wt.-%, more preferably 15 to 75 wt.-%, most preferably 20 to 60 wt.-%, based on the total weight of the curable resin composition.
9. A material according to any one of the preceding claims, wherein The curable resin composition comprises one or more additional reactive diluents selected from the group consisting of styrene and styrene derivatives, epoxides, vinyl ethers, acrylates and methacrylates.
10. A material according to any one of the preceding claims, comprising glass fibres having an aspect ratio in the range 20 to 100,000, preferably 50 to 100,000.
11. The material according to any of the preceding claims, comprising the thermosetting polymer in an amount in the range of 10 wt.-% to 90 wt.-%, based on the total weight of the material.
12. A method for producing a composite glass fiber material, the method comprising contacting glass fibers with a curable resin composition comprising: (i) ethylenically unsaturated resins; and (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I) Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms; wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-% relative to the total amount of reactive diluent (ii) and the further reactive diluent; and curing the curable resin composition to form a thermosetting polymer, thereby obtaining the composite glass fiber material.
13. Use of N-vinyl oxazolidinone of formula (I) in a method for obtaining composite glass fiber materials Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms.
14. The use according to claim 13, wherein A curable resin composition comprising: (i) ethylenically unsaturated resins; and (ii) a reactive diluent which is an N-vinyl oxazolidinone having formula (I); Wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-%, relative to the total amount of reactive diluent (ii) and the further reactive diluent.
15. A curable resin composition comprising (i) ethylenically unsaturated resins; and (ii) a reactive diluent which is an N-vinyl oxazolidinone having the formula (I) Where R 1 , R 2 , R 3 and R 4 are independently selected from a hydrogen atom and an organic moiety containing 1 to 10 carbon atoms; wherein the reactive diluent (ii) is present in an amount of at least 0.5 wt-% relative to the total amount of reactive diluent (ii) and the further reactive diluent; And wherein the ethylenically unsaturated resin (i) is selected from ethylenically unsaturated polyester resins, vinyl ester resins, and combinations thereof.
16. The curable resin composition according to claim 15, wherein The curable resin composition comprises the ethylenically unsaturated resin (i) in an amount of 15 to 85 wt.-%, more preferably 15 to 75 wt.-%, most preferably 20 to 60 wt.-%, based on the total weight of the curable resin composition.
Citation Information
Patent Citations
Preparation of N-vinyl-2-oxazolidinone
US4831153A